Characteristics of centenarians' lifestyles and their contribution to life satisfaction: A case study conducted on Hainan Island. (July 2019) - Hao, Zhe; Chen, Lihong; Li, Yonghua; Zou, Xinqing; Li, Hairong; Feng, Ziyue; Bai, Xuyu; Wang, Zhifu; Qian, Jian; Xu, Yuefeng
Graphical abstract: Highlights: We examined the basic lifestyle characteristics of centenarians in Hainan. Better life conditions contributed to centenarians' life satisfaction. Centenarians with alcohol and tobacco habits were more satisfied with life. Sleep satisfaction was significantly positively correlated with life satisfaction. Abstract: Background: Centenarians represent an intriguing model for healthy aging. They appear to have adapted well to their lives and are likely to be influenced by previous lifestyle habits, and their life satisfaction is influenced by mental and psychological health. Objective: The aim of this study is to explore centenarians' lifestyles by sex and their potential contribution to life satisfaction. Method: In order to examine the common characteristics of centenarians in Hainan and the potential differences between men and women, a cross-sectional survey was conducted with 223 cognitively-intact Chinese centenarians. We also explored the association between life satisfaction and other physical factors using binary logistic regression and principal component analysis. Results: The results provided supplementary evidence indicating that women tended to live longer than men. However, the difference in life satisfaction observed between the sexes was not obvious (p = 0.659). The proportion of physical factors between each sex showed a similar trend in distribution. Most centenarians' lifestyles were similar, in that they followed a light diet and did not smoke or drink alcohol. Centenarians in better physical condition and with higher self-assessment, as well as those with "alcohol and tobacco habits, " were more satisfied with their life. Of the factors examined in the binary logistic regression, sleep satisfaction was the only factor significantly positively correlated with life satisfaction (p < .01). Conclusion: The research findings elucidated physiological and psychological health in centenarians and provided a model of healthy aging strategies for reference purposes.